Using the Weibull distribution to improve the description of riverine wood loads. Issue 4 (22nd August 2016) - Stout, Justin C.; Rutherfurd, Ian; Grove, James; Webb, J. Angus; Kitchingman, Adrian; Tonkin, Zeb
Abstract: Reporting uncertainty in environmental measurements and estimates is important for cross‐comparison and inter‐comparison of sites and other spatial units. One such measure is the load of large in‐stream wood in river systems. In this paper we propose the use of the Weibull distribution to describe the central tendency and variability of wood loads along a river reach. We illustrate the link between the average wood load and the central tendency or scale parameter of the Weibull distribution. The shape of the Weibull distribution is strongly related to the ability of rivers to transport and rearrange the wood in a reach. We use six Victorian rivers to test the fit of the Weibull distribution, showing that the Weibull is a useful and flexible distribution that provides common reporting metrics useful for future studies. Using common reporting metrics provides a stronger tool for comparisons of wood loads between rivers and with reaches. Copyright © 2016 John Wiley & Sons, Ltd.